Role of Zakat in Sustainable Development Goals - Salman Ahmed Shaikh; Abdul Ghafar Ismail (International Journal of Zakat, 2017)
In this paper, we explore the potential of the institution of Zakāt to meet the development challenges, especially in the Muslim world. We discuss the interlinkages between the institution of Zakāt and Maqasid-al-Shari’ah. We also discuss the economic potential and effects of Zakāt by reviewing theoretical and empirical studies. Finally, we also provide our analysis which suggests that Zakāt can play an important role in meeting sustainable development goals related to poverty, hunger, global health and well-being, quality education, decent work and economic growth and income inequality. Keywords: Zakāt, Sustainable Development Goals, Poverty, InequalityJEL Classification Code: E6, H2, H3